Menakar Kembali Akar Ideologi Ormas Radikal-Fundamentalis (Studi Kasus Terhadap Front Pembela Islam (FPI) - Fathor Rahman; Mujahra . (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2017)
FPI is known as radical fundamentalist mass organization. Radical, extreme, and violent attributes to it. This Fact that makes author interested to examinet it. This paper raises the issue of whether there is a correlation between radical, extreme and violent nature practiced by FPI which they believe and understand, or they are like that because of other factors. Then, after analysis, it was found that there was a correlation both of it. FPI become radical fundamentalist mass organization because affected by religious ideology that they understand. FPI ideology tends to the right ideology that is known as hard line Islam. The meaning, eventhougt FPI claims to be a mass organization with a propetic ideology, but their aswaja are not the same as NU’s Aswaja,pesantren and muhammadiyah. Althougt, the authors found that FPI’s ideology is aswaja, follow Imam Al-‘Asy’ari in the field of Aqidah and Imam Syafi’I in the field of Fiqh. The information above is out of sync with other data that also generated from the author’s analysis. The data states that the ideology of FPI aswaja is not same as the mass organization of NU and Muhammadiyah, and this is strengthened by the statement and recognition of FPI stakeholder, that FPI althought taking aswaja as its ideology but not equal to aswaja from the mass of its predecessor.